Cardiovascular effects of mild hypothermia in post-cardiac arrest patients by beat-to-beat monitoring. A single centre pilot study. (June 2014) - Lazzeri, Chiara; Sori, Andrea; Bernardo, Pasquale; Chiostri, Marco; Tommasi, Eleonora; Zucchini, Mery; Romano, Salvatore Mario; Gensini, Gian Franco; Valente, Serafina
Abstract Background: Data on the hemodynamic and cardiovascular effects of hypothermia in patients with cardiac arrest are scarce. The aim of this study was to evaluate the hemodynamic changes induced by hypothermia by means of Most Care® (pressure recording analytical method, PRAM methodology), a beat-to-beat hemodynamic monitoring method. Methods: We enrolled 20 patients with cardiac arrest (CA) consecutively admitted to our intensive cardiac care unit and treated with mild hypothermia (TH). Results: While non-survivors showed no changes in haemodynamic variables throughout the study period, survivors exhibited a significant increase in systemic vascular resistance indexed during hypothermia and a trend towards lower values of heart rate and higher levels of mean arterial pressure. Conclusions: According to our data, PRAM methodology proved to be a feasible and clinically useful tool in CA patients treated with TH since it provides continuous beat-to-beat haemodynamic monitoring that is based on assessment of several haemodynamic variables. Moreover, we observed that survivors showed a different haemodynamic behaviour during hypothermia in respect to patients who died. However, further studies, performed in larger cohorts, are needed to better elucidate the haemodynamic effects of hypothermia in CA patients by means of PRAM methodology.